Youth preference of extreme parks design in urban areas - Khairuddin, Siti Aishah; Mohd Yunus, Mohd Yazid; Othuman Mydin, Md Azree; Ujang, Norsidah (American-Eurasian Network for Scientific Information, 2015)
The term extreme park is a purpose-built recreational environment in urban areas made for extreme activities for skateboarding, bike, and aggressive inline skating, wall climbing and rock climbing for youth to enjoy their leisure time. Lack of appropriate open space areas for youth in urban areas that meet the needs and preferences of youth behaviour are one of the main factors that contribute to social problems. The youth often like to explore the environment and to find a territory of their own and they may avoid the adult spaces, where the teenagers may feel themselves controlled, criticized or excluded. This study attempts to identify youth preferences of extreme park design in urban areas. The survey determined the criteria of successful design criteria that can provide acceptable experiences for users. The study found that most of the respondents preferred to have natural element in develop the extreme park and these findings may be used to expand the current existing guidelines and policies regarding future extreme park development.